Carcinogenic and non-carcinogenic health risks of metal(oid)s in tap water from Ilam city, Iran. (August 2018) - Fakhri, Yadolah; Saha, Narottam; Ghanbari, Sahebeh; Rasouli, Milad; Miri, Ali; Avazpour, Moayed; Rahimizadeh, Aziz; Riahi, Seyed-Mohammad; Ghaderpoori, Mansour; Keramati, Hassan; Moradi, Bigard; Amanidaz, Nazak; et al.
Abstract: One of the most important pathways for exposure to metals is drinking water ingestion. Chronic or acute exposure to metals can endanger the health of the exposed population, and hence, estimation of human health risks is crucial. In the current study for the first time, the concentrations of Mercury (Hg), Arsenic (As), Zinc (Zn), Lead (Pb) and Cobalt (Co) in 120 collected tap water samples (2015, July–November) from Ilam city, Iran were investigated using flame atomic absorption spectrophotometer. Also, the metal-induced carcinogenic and non-carcinogenic risks for consumers exposed to tap drinking water were calculated. The average (range) concentrations of Hg, Zn, As, Pb and Co were defined as 0.40 ± 0.10 μg/L (ND-0.9 μg/L), 5014 ± 5707 μg/L (2900.00–5668.33 μg/L), 21.008 ± 2.876 μg/L (3.5–62 μg/L), 30.38 ± 5.56 μg/L (6–87 μg/L), and 11.34 ± 1.61 μg/L (0.1–50 μg/L), respectively. Average concentrations of all examined metals were significantly higher than WHO and national standard recommended limits. The ranking order of metals concentrations in the tap drinking water was Zn > Pb > As > Co > Hg. Except for Hg and Co, at least one age group consumers were at considerable non-carcinogenic risks induced by Zn, As and Pb [Target Hazard Quotient (THQ > 1)]. The rank order of age groups consumers based on THQ and Incremental lifetime cancer risk (ILCR) was <1 years >1–9 years > 20 + years > 10–19 years. The calculated ILCR for As in all age groups were higher than 10 −3 value. All age groups of consumers in Ilam city, especially infants (<1 years) and children (1–10 years), are at considerable non-carcinogenic and carcinogenesis risk. Graphical abstract: Highlights: Mean concentration of metals was higher than WHO and national standard limits. Populations are exposed to carcinogenic and non-carcinogenic health risks. Infants and children are at higher risk relative to adults.